Anlotinib for the Treatment of Multiple Recurrent Lumbar and Sacral Cord Hemangioblastomas: A Case Report - Jin, Nan; Sun, Chunxiao; Hua, Yijia; Wu, Xinyu; Li, Wei; Yin, Yongmei (Frontiers in Oncology, 2022)
Background Hemangioblastoma (HB) is a rare and highly vascularized tumor that originates from the central nervous system as well as other part of the body. They can appear sporadically or as part of von Hippel–Lindau (VHL) disease, a rare hereditary cancer syndrome. Although surgery can cure the majority of HBs, the disease shows a treatment refractory challenge upon recurrence. HBs express a high amount of vascular endothelial growth factor (VEGF) which is responsible for angiogenesis and subsequently tumor progression. Anti-angiogenic treatment like bevacizumab has showed effect on HB, so we hypothesized that anlotinib could trigger HB regression via its inhibitory effect on VEGF. Case presentation We will share our experience in treating a 62-year-old woman with multiple recurrent lumbar and sacral cord HBs. She was treated with anlotinib (8mg qd d1-14, q3w) for three months and her follow up radiological examination demonstrated marked tumor regression which was evaluated as having partial response pursuant to RECIST 1.1 system. She is currently still receiving treatment of anlotinib orally and the lesions continuously reduced. Conclusion We have reported that anlotinib can cause significant radiographic response in a patient with multiple recurrent lumbar and sacral cord HBs for the first time. This might enable a novel therapeutic approach for patients with multiple recurrent HB or those with multiple lesions such as in VHL disease which are difficult to resect surgically.